Induction of Human Factor VIII Inhibitors in Rats 2: Fine Mapping of Rat anti-Human rFVIII Antibodies - Levin, L G; Jarvis, M; Powell, J; Harrison, J A; Reisner, H M (Thrombosis and Haemostasis, 1996)
Inhibiting antibodies in patients with hemophilia A pose a significant therapeutic dilemma in the treatment of bleeding episodes. The genetic factors which predispose hemophiliacs to inhibitors and the optimal method for inhibitor suppression remain obscure. Hence, an animal model of the human FVIII inhibitor response is of potential value. Sprague-Dawley rats immunized with human recombinant FVIII (rFVIII) subsequently developed abnormal coagulation parameters coincident with the development of an immune response to the human protein. The epitopes for the resultant rat anti-rFVIII antibodies were mapped using a random fragment expression library constructed from the FVIII cDNA. Antigenic regions located within the Al, First and Second Acidic and B domains were mapped. Rat immunoglobulins reactive with the individual epitopes were immunoaffinity purified and assayed for inhibitory activity. Several of the epitopes mapped using the rat antibodies were similar to regions previously shown to be antigenic for human inhibitors. By contrast, no epitopes were mapped to the A2 domain with the techniques used. This may be due to the possible presence of conformational epitopes in this area which cannot undergo fragmentation and still retain antigenicity or the presence of relatively low concentrations of antibodies to this region. The rat model shares some similarity with both the auto- and alloimmune human response to FVIII and therefore may be a valuable model for studies on the induction and suppression of the inhibitor response.